2020
DOI: 10.1136/jim-2019-001254
|View full text |Cite
|
Sign up to set email alerts
|

Association between C Reactive Protein and Depression in a Population of Healthy Adults: The Cooper Center Longitudinal Study

Abstract: The relationship between depression and inflammation is currently a topic of much interest. Previous studies have produced mixed results regarding the association between depression and high-sensitivity C reactive protein (hs-CRP). The aim of this report was to determine the association between hs-CRP and depression in a large sample of healthy adults. This is a cross-sectional study of 26,638 healthy adults seen for preventive medical examinations between December 2000 and August 2018 at the Cooper Clinic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(68 reference statements)
0
7
1
Order By: Relevance
“…Overall, the present systematic review reported that most studies here retrieved, found a positive association between elevated CRP levels and depression [29,51,52,54,55,61,63,64,66,67,[69][70][71][72][73]80,81,83,[90][91][92][93][94]100]. Conversely, other studies did not confirm this association [49,50,62,68,74,76,86,88,89].…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Overall, the present systematic review reported that most studies here retrieved, found a positive association between elevated CRP levels and depression [29,51,52,54,55,61,63,64,66,67,[69][70][71][72][73]80,81,83,[90][91][92][93][94]100]. Conversely, other studies did not confirm this association [49,50,62,68,74,76,86,88,89].…”
Section: Discussioncontrasting
confidence: 53%
“…Another cross-sectional study, including 9459 Chinese middle-aged and elderly participants of the China Health and Retirement Longitudinal Study, did not find any correlation between CRP levels and depressive symptoms after adjusting for confounders [76]. A recent large cross-sectional study assessing serum hs-CRP levels and depression symptoms using CESD, in 26,638 healthy adults, recruited at the Cooper Clinic in Dallas, Texas, reported an association between hs-CRP levels and depression which could be more likely explained by obesity status [62]. An observational study investigated the association between CRP levels and depression also considering shared genetic and environmental factors [75].…”
Section: Cross-sectional Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…While it may have been expected that both biomarkers rise and fall in unison (suggesting the possibility of a distinctive mechanism of concurrent inflammatory activity), given that CRP is a good indication of muscle inflammation, this slight rise (staying within normal values) may be explained by the physical activity of the treks [ 44 ]. Given known associations between symptoms of depression and anxiety and acute inflammation [ 45 , 46 ] and the secretion of pro-inflammatory cytokines [ 47 , 48 ], it is important to advance our understanding of how immersive experiences in nature might “get under the skin”. This said, the evaluation design and very small sample of these biomarker analyses place these findings at the very preliminary level of understanding, which should be considered when interpreting these results.…”
Section: Discussionmentioning
confidence: 99%
“…Among the commonly used biomarkers, recent studies have demonstrated that lower uric acid and higher C-reactive protein levels are independently associated with depression. 6,7) The association between serum cholesterol levels and depression has continuously been reported over the past decades, based on a possible mechanism between cholesterol and serotonin. 8,9) A recent metaanalysis, in 2016, 10) demonstrated a cross-sectional link between depression and low serum low-density lipoprotein cholesterol (LDL-C) levels, using serum LDL-C as a continuous variable.…”
Section: Introductionmentioning
confidence: 99%